Statistical analyses for criminal justice and criminoloy : a conceptual introduction - DeValve, Michael J. (New York, NY ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2024)
"This book is a how-to guide on statistical analyses designed for undergraduates and others new to the subject. It uses a conceptual framework, starting with the most basic concepts of statistics and moving up through the capacity to perform bivariate regression. Written in an easy-going and clear style, it uses policing data to illustrate concepts. Easily identified Main Take-Aways and Key Terms features aid student understanding. Designed to combat the fear of mathematics and statistics often held by students in the social sciences, plain verbiage, multiple examples, and clear demonstrations combine to achieve the actualization and proper contextualized use of univariate and bivariate statistics. This work also serves as a launching pad for further study in statistics. As an accessible introduction to statistics in criminal justice and criminology, this text will appeal to both students and instructors in introductory criminal justice and criminology statistics courses."
Includes bibliographical references and index/Rujukan : mukasurat
Keywords: Criminal justice, Administration of; Criminology; Criminal statistics